Forecasting the electronification of payments with learning curves: The case of Finland - Jussi Snellman; Jukka Vesala (Bank of Finland, 1999)
This paper examines the electronification of noncash payments in Finland and the extent to which noncash payment means are used as substitutes for cash. We model the processes of cash substitution and electronification of payments as 'S'-shaped learning curves and generate forecasts by extrapolating these curves. The 'S'-shaped learning curves fit the data well. Our results indicate that in Finland the cash substitution process as a whole is approaching the saturation point. Although the electronification process is clearly ongoing as regards larger-value bill payments, for small-value point-of-sale payments we seem to have reached saturation. Electronification of payments, having progressed swiftly and extensively in Finland, is already beginning to slow down. We conclude the paper with a discussion of the reasons for this turn of events and of the different factors that affect the speed of diffusion of new means of payment.
URN:NBN:fi:bof-201501291030
Keywords: 330; payments; electronification; learning curves